Supporting Students in Developing Mathematics Learning Media for Fractions Topic - Setiyani, Eka Denti; Partono, Partono; Nusantara, Duano Sapta; Maphutha, Kgaladi (Jurnal Sains Sosio Humaniora, 2025)
This study aims to address the challenges faced by seventh-grade students in understanding fraction concepts, particularly their difficulties in both conceptualizing and applying fractions in real-life contexts. To tackle these issues, a training program was designed to enhance students' creativity and improve their comprehension of fractions through the development of mathematics learning media. The training was specifically conducted at MTs Miftahul Ulum, and it employed a two-phase methodology. The first phase involved the delivery of instructional content on fractions, while the second phase focused on guiding students in the creation of simple, yet effective, mathematics learning media. The results of the training indicated a high level of engagement and enthusiasm among participants, as demonstrated by their active involvement in the media creation process. This study contributes to the pedagogical field by providing an innovative approach for supporting students in designing and utilizing learning media, ultimately fostering a more interactive and engaging learning environment. It is anticipated that the knowledge gained from this training will empower students to design creative learning tools that can enhance their understanding of mathematical concepts, particularly fractions.